Heat shrinkable polyester label film and preparation method and container thereof
By developing a characteristic heat-shrinkable polyester label film, the problem that the existing label film is difficult to detach the container under low temperature conditions is solved, and efficient detachment and good recycling and reuse effects in the washing liquid above 50°C are achieved.
Patent Information
- Application Number
- CN202111252439.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-22
- Filing Date
- 2021-10-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-10-27
AI Technical Summary
The existing label film is difficult to detach from the container under low temperature conditions, resulting in low recycling and reuse efficiency.
A heat-shrinkable polyester label film is used, which is formed by polycondensation reaction of a specific composition, with a glass transfer temperature of 50°C to 65°C and a thermal enthalpy below 15 J/g, and a film with high shrinkage rate and strong shrinkage force is obtained by preheating, stretching and annealing treatment.
In the washing liquid above 50°C, the heat-shrinkable polyester label film can effectively detach the container, improve recycling efficiency, and maintain good appearance and impact fracture resistance.
Smart Images

Figure BDA0003322876640000141 
Figure BDA0003322876640000151 
Figure BDA0003322876640000152
Abstract
Description
Technical Field
[0001] The invention relates to a polyester label film and a preparation method thereof, in particular to a heat shrinkable polyester label film and a preparation method thereof. Background Art
[0002] With the rise of global environmental awareness, the issue of recycling and reuse of containers such as plastic bottles has attracted attention. Generally speaking, one of the processes of recycling and reuse of containers is to remove the label film on the container from the container. At present, most of the widely used label films are plastic label films, and the plastic label films are firmly attached to the container through adhesive components, so that the plastic label films need to be treated with alkaline liquid or immersed in hot water at 80°C to 90°C to effectively remove the plastic label films from the container. Therefore, based on the consideration of recycling and reuse, the development of label films that can be easily removed from the container is currently a widely studied issue.
[0003] US Patent Publication No. US6680097B1 discloses a label film that can be attached to a recyclable container. The label film includes a heat-shrinkable stretch plastic film layer and an adhesive layer. Through the aforementioned layer structure design, when the container is placed in an alkaline washing liquid above 50°C, the adhesive layer loses its adhesiveness and the heat-shrinkable stretch plastic film layer shrinks, thereby causing the label film to fall off the container. In addition, the patent case only shows in FIG. 3 that the shrinkage rate of the label film in the machine direction at 80°C is less than 10%. It can be seen that the patent case No. US6680097B1 does not disclose the relevant content of the shrinkage rate and shrinkage force when immersed in hot water at 55°C, and under the premise that the shrinkage rate of the label film at 80°C is less than 10%, it can be reasonably expected that the label film will hardly shrink under low temperature conditions, such as 50°C to 60°C. Therefore, the label film should not be easy to fall off from the container at low temperatures, and there is a problem of poor label removal effect.
[0004] U.S. Patent Publication No. US9978291B2 discloses a label film attached to a container. The label film comprises a biaxially stretched polymer film layer, a printed decorative layer and a pressure-sensitive adhesive layer. In a hot washing liquid at 50°C to 95°C, the shrinkage of the biaxially stretched polymer film layer of the label film in the machine direction and the perpendicular machine direction is less than 65%, and the difference between the shrinkage in the machine direction and the shrinkage in the perpendicular machine direction is less than 50%. At the same time, the shrinkage force of the biaxially stretched polymer film layer in hot water at 60°C is 3.5N / mm 2Below. Under such a design, when the adhesion between the label film and the container is high, the label film can be washed off the container when immersed in the hot washing liquid, and will not shrink sharply to cause the label film to split or the printed decorative layer to remain on the container. However, the patent case No. US9978291B2 does not disclose the composition design of the biaxially stretched polymer film layer, nor does it disclose the preparation process of the biaxially stretched polymer film layer. In addition, the patent case only provides that the shrinkage rate is designed to be less than 65% and the shrinkage force is designed to be 3.5N / mm at 60°C. 2 The following suggestions, however, do not disclose anything related to the shrinkage rate and shrinkage force at 55°C.
[0005] US Patent Publication No. US5070180A discloses a shrink copolyester film used as a sleeve label film for polyethylene terephthalate containers. The shrink copolyester film comprises a copolyester. The copolyester is formed by a polycondensation reaction of an acid component and an alcohol component. The acid component comprises 50 mol% to 99 mol% of terephthalic acid, 1 mol% to 25 mol% of an aliphatic dicarboxylic acid, and 0 mol% to 30 mol% of an aromatic dicarboxylic acid. The alcohol component comprises 70 mol% to 100 mol% of ethylene glycol, and 0 mol% to 30 mol% of a diol compound, wherein the diol compound is selected from neopentyl glycol, propylene glycol, butanediol, hexanediol, diethylene glycol, polyalkylene glycol, or cyclohexanedimethanol. The shrinkage rate of the shrink copolyester film at 100°C is above 30%, and the glass transition temperature of the shrink copolyester film is 35°C to 65°C. In such a design, when the shrink copolyester film is sleeved on the polyethylene terephthalate container, it can shrink evenly without wrinkles or deformation. From the overall content of the patent case No. US5070180A, it can be seen that the design concept of the shrink copolyester film is to enable the shrink copolyester film to shrink and firmly adhere to the container, and there is no wrinkle defect caused by film shrinkage in appearance, but the overall content does not have any content related to label film, and even does not disclose how to remove the shrink copolyester film from the container and the effect.
[0006] Japanese Patent Publication No. JP3829353B2 discloses a heat-shrinkable polyester film as a sleeve label film. The heat-shrinkable polyester film comprises polyester, and the polyester is formed by polycondensation of a dicarboxylic acid component, a diol component and other components. The dicarboxylic acid component comprises more than 70 mol% of terephthalic acid, and the diol component comprises more than 70 mol% of ethylene glycol. The other components comprise at least one of adipic acid, butylene glycol isophthalate and neopentyl glycol. The maximum shrinkage force of the heat-shrinkable polyester film is 0.5 kg / mm 2 Up to 1.2kg / mm 2, and the shrinkage rate after being immersed in hot water at 75°C for 10 seconds is less than 40%, and the shrinkage rate after being immersed in hot water at 95°C for 10 seconds is more than 50%. In such a design, the heat-shrinkable polyester film can shrink evenly when it is sleeved on a container without wrinkles or shrinkage spots, and has excellent impact resistance. From the overall content of the patent case No. JP3829353B2, it can be seen that the design concept of the heat-shrinkable polyester film is to enable the heat-shrinkable polyester film to shrink and be firmly sleeved on the container, and there is no wrinkle defect caused by film shrinkage in appearance, but the overall content does not have any content related to labeling film, and there is no content related to how to make the heat-shrinkable polyester film detach from the container, and there is no content related to the shrinkage rate and shrinkage force when immersed in hot water at 55°C.
[0007] Chinese Patent Publication No. CN112679709A discloses a polyester for heat shrinkable film, and the polyester for heat shrinkable film contains 3-8wt% dicarboxylic acid, 5-15wt% aliphatic diol, 0.001-0.003wt% hydrophilic modifier, 0.0001-0.0005wt% antioxidant heat stabilizer, and the remaining molar ratio of terephthalic acid or terephthalic acid derivative to ethylene glycol is 1:1.0-2.5. Based on the above design, the heat shrinkable film formed by the heat shrinkable film polyester has a high shrinkage rate. However, the overall content of the patent case No. CN112679709A does not contain any content related to being able to detach from the container in hot water below 80°C, nor does it contain any content related to the shrinkage rate and shrinkage force when immersed in hot water at 55°C.
[0008] U.S. Patent Publication No. US2013 / 0011587A1 discloses a heat-shrinkable polyester film attached to a container. The heat-shrinkable polyester film comprises a polyester resin matrix and particles distributed in the polyester resin matrix. The polyester resin matrix comprises a copolyester, and the copolyester is formed by a polycondensation reaction of a dicarboxylic acid component and a diol component, wherein the dicarboxylic acid component comprises more than 80 mol% of terephthalic acid, and the diol component comprises ethylene glycol and 14 mol% to 24 mol% of other diols. The opacity of the heat-shrinkable polyester film is 20% to 70%, and the heat-shrinkable polyester film is immersed in hot water at 90°C for 10 seconds, and the shrinkage rate in the maximum shrinkage direction is 40% to 80%. Based on such a design, the container attached with the heat-shrinkable polyester film is immersed in hot water at 80°C, and the heat-shrinkable polyester film can be detached from the container. However, the patent case No. US2013 / 0011587A1 only proposes that the heat-shrinkable polyester film can be detached from the container in hot water at 80°C, but the overall content does not disclose how the heat-shrinkable polyester film can be detached from the container in hot water below 80°C, nor does it disclose the shrinkage rate and shrinkage force when immersed in hot water at 55°C.
[0009] U.S. Patent Publication No. US8815994B2 discloses a heat-shrinkable polyester film. The heat-shrinkable polyester film comprises a polyester resin matrix and particles dispersed in the polyester resin matrix. The polyester resin matrix comprises a copolyester, and the copolyester is formed by a polycondensation reaction of a dicarboxylic acid component and a diol component, wherein the dicarboxylic acid component comprises at least one of terephthalic acid and dimethyl terephthalate, and the diol component comprises ethylene glycol and 2,2-dimethyl (1,3-propane) diol. The haze of the heat-shrinkable polyester film is 80% to 95%, and when immersed in hot water at 90°C for 10 seconds, the shrinkage rate of the heat-shrinkable polyester film in the maximum shrinkage direction is 40% to 80%. Based on such a design, when a container with the heat-shrinkable polyester film is immersed in hot water at 80°C, the heat-shrinkable polyester film can be peeled off from the container. However, the patent case No. US8815994B2 only proposes that the heat-shrinkable polyester film can be detached from the container in hot water at 80°C, but the overall content does not disclose how the heat-shrinkable polyester film can be detached from the container in hot water below 80°C, nor does it disclose the shrinkage rate and shrinkage force when immersed in hot water at 55°C. Summary of the invention
[0010] Therefore, the first object of the present invention is to provide a heat-shrinkable polyester label film that can be separated from a container by being immersed in a cleaning solution (such as hot water or sodium hydroxide aqueous solution) at a temperature above 50°C.
[0011] Therefore, the heat-shrinkable polyester label film of the present invention has the following properties: when placed in 55°C hot water for 30 seconds, the shrinkage force in at least one shrinkage direction is 5.5N or more; and when placed in 55°C hot water for 240 seconds, the shrinkage rate in the shrinkage direction is 50% or more.
[0012] In the heat-shrinkable polyester label film of the present invention, the heat-shrinkable polyester label film also has the following properties:
[0013] (1) when placed in hot water at 55°C for 10 seconds, the shrinkage in the shrinkage direction is 5% or more; and
[0014] (2) When placed in hot water at 55° C. for 30 seconds, the shrinkage rate in the shrinkage direction is 20% or more.
[0015] In the heat-shrinkable polyester label film of the present invention, the heat-shrinkable polyester label film also has the following properties:
[0016] When placed in hot water at 95° C. for 10 seconds, the shrinkage rate in the shrinkage direction is 65% or more.
[0017] In the heat-shrinkable polyester label film of the present invention, the shrinkage force of the heat-shrinkable polyester label film in the shrinkage direction is 5.5N to 10N when placed in 55°C hot water for 30 seconds.
[0018] In the heat-shrinkable polyester label film of the present invention, the aging natural shrinkage rate of the heat-shrinkable polyester label film is less than 3.2%, and the aging natural shrinkage rate is measured under the conditions of 40° C. and 40% relative humidity for 672 hours.
[0019] In the heat-shrinkable polyester label film of the present invention, the glass transition temperature of the heat-shrinkable polyester label film is 50°C to 65°C.
[0020] The second object of the present invention is to provide a heat-shrinkable polyester label film that can be separated from a container by being immersed in a cleaning solution (such as hot water or sodium hydroxide aqueous solution) at a temperature above 50°C.
[0021] The heat shrinkable polyester label film of the present invention comprises at least one polyester, and the polyester is formed by a reaction of a composition, and the composition comprises a dicarboxyl (-COO-) series mixture and a diol series mixture. The heat shrinkable polyester label film has a glass transition temperature of 50°C to 65°C and a thermal enthalpy of less than 15 J / g, and the heat shrinkable polyester label film has a shrinkage force of more than 5.5 N in at least one shrinkage direction when placed in 55°C hot water for 30 seconds.
[0022] The dicarboxyl-based mixture comprises a dicarboxyl compound and a chain hydrocarbon dicarboxylic acid compound, wherein the dicarboxyl compound is selected from terephthalic acid or dimethyl terephthalate, and the content of the chain hydrocarbon dicarboxylic acid compound ranges from greater than 0 mol% to 7 mol%, based on the total amount of the dicarboxyl-based mixture being 100 mol%. The diol-based mixture comprises ethylene glycol and a diol compound, and the diol compound does not include ethylene glycol.
[0023] In the heat-shrinkable polyester label film of the present invention, the chain hydrocarbon dicarboxylic acid compound is selected from a straight-chain hydrocarbon dicarboxylic acid compound, a branched-chain hydrocarbon dicarboxylic acid compound or a combination thereof.
[0024] In the heat-shrinkable polyester label film of the present invention, the straight-chain hydrocarbon-based dicarboxylic acid compound is selected from adipic acid, succinic acid, azelaic acid or any combination thereof.
[0025] In the heat-shrinkable polyester label film of the present invention, the diol compound is selected from diol compounds having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group, branched hydrocarbon diol compounds, or a combination thereof.
[0026] In the heat-shrinkable polyester label film of the present invention, the diol compound having a linear hydrocarbon group or a linear hydrocarbon oxy group is selected from 1,4-butanediol, diethylene glycol, hexanediol, 1,3-propylene glycol, triethylene glycol, polyethylene glycol or any combination thereof.
[0027] In the heat-shrinkable polyester label film of the present invention, the branched hydrocarbon diol compound is selected from neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol or any combination thereof.
[0028] In the heat-shrinkable polyester label film of the present invention, based on 100 mol % of the total amount of the diol mixture, the content of the diol compound is greater than 30 mol %.
[0029] In the heat-shrinkable polyester label film of the present invention, the shrinkage force of the heat-shrinkable polyester label film in the shrinkage direction is 5.5N to 10N when placed in 55°C hot water for 30 seconds.
[0030] In the heat-shrinkable polyester label film of the present invention, the aging natural shrinkage rate of the heat-shrinkable polyester label film is less than 3.2%, and the aging natural shrinkage rate is measured under the conditions of 40° C. and 40% relative humidity for 672 hours.
[0031] In the heat-shrinkable polyester label film of the present invention, the glass transition temperature of the heat-shrinkable polyester label film is 50°C to 62°C.
[0032] In the heat-shrinkable polyester label film of the present invention, the heat-shrinkable polyester label film has the following properties:
[0033] When placed in hot water at 55° C. for 240 seconds, the shrinkage rate in the shrinkage direction is 50% or more.
[0034] In the heat-shrinkable polyester label film of the present invention, the heat-shrinkable polyester label film has at least one of the following properties:
[0035] (1) when placed in hot water at 55°C for 10 seconds, the shrinkage in the shrinkage direction is 5% or more; and
[0036] (2) When placed in hot water at 55° C. for 30 seconds, the shrinkage rate in the shrinkage direction is 20% or more.
[0037] In the heat-shrinkable polyester label film of the present invention, the heat-shrinkable polyester label film has the following properties:
[0038] When placed in hot water at 95° C. for 10 seconds, the shrinkage rate in the shrinkage direction is 65% or more.
[0039] The third object of the present invention is to provide a method for preparing a heat-shrinkable polyester label film, which can obtain a heat-shrinkable polyester label film that can be separated from a container by being immersed in a washing liquid (such as hot water or sodium hydroxide aqueous solution) at a temperature above 50°C.
[0040] The method for preparing the heat shrinkable polyester label film of the present invention comprises the following steps:
[0041] (a) forming an unstretched sheet from a polyester component comprising at least one polyester, wherein the polyester is formed by reacting a composition comprising a dicarboxyl (-COO-) series mixture and a diol series mixture;
[0042] The dicarboxyl-based mixture comprises a dicarboxyl compound and a chain hydrocarbon dicarboxylic acid (-COOH) compound, wherein the dicarboxyl compound is selected from terephthalic acid or dimethyl terephthalate, and based on the total amount of the dicarboxyl-based mixture being 100 mol%, the content of the chain hydrocarbon dicarboxylic acid compound is in a range of greater than 0 mol% to 7 mol%; and
[0043] The diol mixture comprises ethylene glycol and a diol compound, and the diol compound does not include ethylene glycol; and
[0044] (b) subjecting the unstretched sheet to a preheating treatment, a stretching treatment and an annealing treatment in sequence, wherein the temperature range of the annealing treatment is from -5°C to +10°C of the glass transition temperature of the unstretched sheet.
[0045] In the method for preparing the heat-shrinkable polyester label film of the present invention, the chain hydrocarbon dicarboxylic acid compound is selected from a straight-chain hydrocarbon dicarboxylic acid compound, a branched-chain hydrocarbon dicarboxylic acid compound or a combination thereof.
[0046] In the method for preparing the heat-shrinkable polyester label film of the present invention, the straight-chain hydrocarbon-based dicarboxylic acid compound is selected from adipic acid, succinic acid, azelaic acid or any combination thereof.
[0047] In the method for preparing the heat-shrinkable polyester label film of the present invention, the diol compound is selected from diol compounds having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group, branched hydrocarbon diol compounds, or a combination thereof.
[0048] In the method for preparing the heat-shrinkable polyester label film of the present invention, the diol compound having a linear hydrocarbon group or a linear hydrocarbon oxy group is selected from 1,4-butanediol, diethylene glycol, hexanediol, 1,3-propylene glycol, triethylene glycol, polyethylene glycol or any combination thereof.
[0049] In the method for preparing the heat-shrinkable polyester label film of the present invention, the branched hydrocarbon diol compound is selected from neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol or any combination thereof.
[0050] In the method for preparing the heat-shrinkable polyester label film of the present invention, based on the total amount of the diol mixture being 100 mol %, the content of the diol compound is in a range of 30 mol % or more.
[0051] In the method for preparing the heat-shrinkable polyester label film of the present invention, in step (a), the polyester component is subjected to a melting treatment and an extrusion treatment to obtain the unstretched sheet, and the temperature range of the melting treatment is 210° C. to 260° C.
[0052] In the method for preparing the heat-shrinkable polyester label film of the present invention, the stretching treatment is performed by stretching the unstretched sheet material 3 to 7 times along a stretching direction, and the stretching direction is the machine direction or perpendicular to the machine direction.
[0053] In the preparation method of the heat-shrinkable polyester label film of the present invention, the stretching treatment is carried out by stretching the unstretched sheet along two stretching directions, wherein one stretching direction is the machine direction and the other stretching direction is perpendicular to the machine direction, and the stretching in one of the stretching directions is greater than 1 to 2 times, and the stretching in the other stretching direction is 3 to 7 times.
[0054] The fourth object of the present invention is to provide a container.
[0055] The container of the present invention comprises: the above-mentioned heat-shrinkable polyester label film attached to the surface of the container.
[0056] The effect of the present invention is that, through the design of the shrinkage force and the shrinkage rate, when the heat-shrinkable polyester label film of the present invention is attached to a container, the heat-shrinkable polyester label film of the present invention can be separated from the container by being immersed in a washing liquid (such as hot water or sodium hydroxide aqueous solution) above 50°C, and has a good label removal rate. In addition, through the design of the composition, glass transition temperature, thermal enthalpy and shrinkage force, the heat-shrinkable polyester label film of the present invention can also be separated from the container by being immersed in a washing liquid (such as hot water or sodium hydroxide aqueous solution) above 50°C, and has a good label removal rate. DETAILED DESCRIPTION
[0057] The present invention will be described in detail below.
[0058] [Heat Shrinkable Polyester Label Film]
[0059] The heat shrinkable polyester label film has a glass transition temperature of 50°C to 65°C and a thermal enthalpy of less than 15 J / g, and the shrinkage force of the heat shrinkable polyester label film in at least one shrinkage direction is greater than 5.5 N when placed in 55°C hot water for 30 seconds. The heat shrinkable polyester label film comprises at least one polyester, and the polyester is formed by a reaction of a composition, and the composition comprises a dicarboxyl (-COO-) series mixture and a diol series mixture. The dicarboxyl series mixture comprises a dicarboxyl compound and a chain hydrocarbon series dicarboxylic acid compound, the dicarboxyl compound is selected from terephthalic acid or dimethyl terephthalate, and the content of the chain hydrocarbon series dicarboxylic acid compound ranges from greater than 0 mol% to 7 mol%, based on the total amount of the dicarboxyl series mixture being 100 mol%. The diol series mixture comprises ethylene glycol and a diol compound, and the diol compound does not include ethylene glycol.
[0060] In order to make the heat shrinkable polyester label film have a better label removal rate, preferably, the glass transition temperature of the heat shrinkable polyester label film is 50° C. to 62° C.
[0061] The thermal enthalpy can be adjusted by the composition, dosage, process parameters, etc. In some embodiments of the present invention, the thermal enthalpy is 5 J / g to 13 J / g.
[0062] The shrinking direction is, for example, the machine direction (MD) or the transverse direction (TD). In order to make the heat shrinkable polyester label film have a better label removal rate, preferably, the heat shrinkable polyester label film is placed in 55°C hot water for 30 seconds, and the shrinkage force in the shrinking direction is 5.5N to 10N. In some embodiments of the present invention, the aging natural shrinkage rate of the heat shrinkable polyester label film is less than 3.2%, and the aging natural shrinkage rate is measured under the conditions of 40°C and a relative humidity of 40% for 672 hours. In some embodiments of the present invention, the aging natural shrinkage rate of the heat shrinkable polyester label film is 0.1% to 3.2%.
[0063] In some embodiments of the present invention, the heat-shrinkable polyester label film has the following properties: when placed in 55°C hot water for 240 seconds, the shrinkage rate in the shrinkage direction is 50% or more. In addition, in some embodiments of the present invention, the heat-shrinkable polyester label film also has at least one of the following properties: (i) when placed in 55°C hot water for 10 seconds, the shrinkage rate in the shrinkage direction is 5% or more; (ii) when placed in 55°C hot water for 30 seconds, the shrinkage rate in the shrinkage direction is 20% or more.
[0064] In some embodiments of the present invention, the heat-shrinkable polyester label film has the following properties: when placed in 95° C. hot water for 10 seconds, the shrinkage rate in the shrinkage direction is greater than 65%.
[0065] In some embodiments of the present invention, the chain hydrocarbon dicarboxylic acid compound is selected from a straight-chain hydrocarbon dicarboxylic acid compound, a branched hydrocarbon dicarboxylic acid compound or a combination thereof. The straight-chain hydrocarbon dicarboxylic acid compound is, for example, but not limited to, adipic acid, succinic acid or azelaic acid. In some embodiments of the present invention, the straight-chain hydrocarbon dicarboxylic acid compound is selected from adipic acid, succinic acid, azelaic acid or any combination thereof. In some embodiments of the present invention, based on the total amount of the dicarboxyl-based mixture as 100 mol%, the content of the chain hydrocarbon dicarboxylic acid compound ranges from 1 mol% to 7 mol%.
[0066] The diol compound is, for example, but not limited to, an aliphatic diol compound or an aromatic diol compound. The aliphatic diol compound is, for example, but not limited to, a diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group or a branched hydrocarbon diol compound. In some embodiments of the present invention, the diol compound is selected from a diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group, a branched hydrocarbon diol compound, or a combination thereof. The diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group is, for example, but not limited to, 1,4-butanediol, diethylene glycol, hexanediol, 1,3-propylene glycol, triethylene glycol, or polyethylene glycol (PEG for short). In some embodiments of the present invention, the diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group is selected from 1,4-butanediol, diethylene glycol, hexanediol, 1,3-propylene glycol, triethylene glycol, polyethylene glycol, or any combination thereof. The branched hydrocarbon diol compound is, for example, neopentyl glycol, 2-methyl-1,3-propanediol or 2-ethyl-2-butyl-1,3-propanediol. In some embodiments of the present invention, the branched hydrocarbon diol compound is selected from neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol or any combination thereof. In some embodiments of the present invention, the content of the diol compound is 30 mol% or more based on the total amount of the diol mixture as 100 mol%. In some embodiments of the present invention, the content of the diol compound is 30 mol% to 40 mol% based on the total amount of the diol mixture as 100 mol%.
[0067] [Heat Shrinkable Polyester Label Film]
[0068] In addition to satisfying the above-mentioned requirement of being able to be detached from a container and having a good label removal rate when immersed in a washing liquid above 50°C through the design of the above-mentioned composition, glass transition temperature, thermal enthalpy and shrinkage force, the heat shrinkable polyester label film of the present invention can also achieve the requirement by being designed to meet the following properties: when placed in 55°C hot water for 30 seconds, the shrinkage force in the shrinkage direction is 5.5N or more; and when placed in 55°C hot water for 240 seconds, the shrinkage rate in the shrinkage direction is 50% or more.
[0069] In some embodiments of the present invention, the heat-shrinkable polyester label film also has the following properties: when placed in 55°C hot water for 10 seconds, the shrinkage rate in the shrinkage direction is greater than 5%; when placed in 55°C hot water for 30 seconds, the shrinkage rate in the shrinkage direction is greater than 20%.
[0070] The other detailed descriptions are the same as those of the above-mentioned heat shrinkable polyester label film, so they are not repeated here.
[0071] [Method for preparing heat shrinkable polyester label film]
[0072] The method for preparing the heat shrinkable polyester label film of the present invention comprises the following steps:
[0073] Step (a), forming an unstretched sheet from a polyester component comprising at least one polyester, wherein the polyester is formed by a reaction of a composition, and the composition comprises a dicarboxyl mixture and a diol mixture. The dicarboxyl mixture comprises a dicarboxyl compound and a chain hydrocarbon dicarboxylic acid compound. The dicarboxyl compound is selected from terephthalic acid or dimethyl terephthalate, and the content of the chain hydrocarbon dicarboxylic acid compound ranges from greater than 0 mol% to 7 mol%, based on the total amount of the dicarboxyl mixture being 100 mol%. The diol mixture comprises ethylene glycol and a diol compound, and the diol compound does not include ethylene glycol; and
[0074] Step (b) sequentially preheats, stretches and anneals the unstretched sheet, wherein the annealing temperature ranges from the glass transition temperature of the unstretched sheet minus 5 degrees Celsius (i.e., the glass transition temperature -5°C) to the glass transition temperature plus 10 degrees Celsius (i.e., the glass transition temperature +10°C).
[0075] <Step (a)>
[0076] The thickness of the unstretched sheet can be the thickness of the unstretched sheet used to form the polyester heat shrinkable film in the past, or can be adjusted according to the requirements of the object to which the polyester heat shrinkable film is applied. In some embodiments of the present invention, the thickness range of the unstretched sheet is less than 1 mm. In some embodiments of the present invention, the thickness range of the unstretched sheet is 150 μm to 500 μm. In some embodiments of the present invention, the thickness range of the unstretched sheet is 190 μm to 275 μm. The chain hydrocarbon dicarboxylic acid compound and the diol compound are as described above, so they are not repeated here.
[0077] In some embodiments of the present invention, the polyester component is subjected to melt processing and extrusion processing to obtain the unstretched sheet.
[0078] In some embodiments of the present invention, the temperature range of the melt treatment is 210°C to 260°C.
[0079] <Step (b)>
[0080] The preheating treatment is to soften the unstretched sheet so that the stretching treatment can be performed. The temperature of the preheating treatment is adjusted according to the material of the unstretched sheet and the requirements of the stretching treatment. In some embodiments of the present invention, the preheating temperature of the preheating treatment ranges from 60°C to 120°C. In some embodiments of the present invention, the temperature of the stretching treatment ranges from 30°C to 100°C.
[0081] In some embodiments of the present invention, the stretching process is performed by stretching the unstretched sheet material along a stretching direction, and the stretching direction is a machine direction or a perpendicular machine direction. In some embodiments of the present invention, the stretching process is performed by stretching at a stretching ratio of 3 to 7 times. In some embodiments of the present invention, the stretching process is performed by stretching at a stretching ratio of 4 to 6 times.
[0082] In some embodiments of the present invention, the stretching process is performed by stretching the unstretched sheet material along two stretching directions, wherein one stretching direction is a machine direction and the other stretching direction is perpendicular to the machine direction. In some embodiments of the present invention, under the design of the stretching direction, the stretching process in one of the stretching directions is performed at a stretching ratio of greater than 1 to 2 times, and the stretching process in the other stretching direction is performed at a stretching ratio of 3 to 7 times. In some embodiments of the present invention, under the design of the stretching direction, the stretching process in one of the stretching directions is performed at a stretching ratio of greater than 1 to 1.4 times, and the stretching process in the other stretching direction is performed at a stretching ratio of 4 to 6 times.
[0083] <Container>
[0084] The container of the present invention comprises a heat shrinkable polyester label film attached to the surface of the container. The container is, for example, a glass container or a polymer container. The heat shrinkable polyester label film is as described above, so it will not be described in detail.
[0085] The present invention will be further described with reference to the following examples, but it should be understood that the examples are only for illustration and should not be construed as limitations of the present invention.
[0086] Preparation Example 1: First Polyester Pellets
[0087] An acid component including 100 mol% of terephthalic acid, an alcohol component including 78.7 mol% of ethylene glycol and 21.3 mol% of neopentyl glycol, and 300 ppm of tetraethylammonium hydroxide are mixed to form a mixture. The mixture is heated to 250°C and subjected to an esterification reaction under a nitrogen atmosphere. When the amount of water distilled reaches the theoretical value of the esterification reaction, 340 ppm of ethylene glycol antimony (as a catalyst) and 100 ppm of trimethyl phosphate (as a thermal stabilizer) are added, and a polymerization reaction is carried out under a vacuum environment of 275°C to form a first polyester pellet having an intrinsic viscosity (IV) of 0.67 dL / g and a glass transition temperature of 75°C.
[0088] Preparation Example 2 Second Polyester Pellets
[0089] The polybutylene terephthalate pellets were purchased from Changchun Man-Made Resin Co., Ltd. and had a model number of 1100-211D. The polybutylene terephthalate pellets had an intrinsic viscosity of 0.75 dL / g and a glass transition temperature of 45°C.
[0090] Preparation Example 3 The third polyester pellet
[0091] An acid component including 73.0 mol% of terephthalic acid and 27.0 mol% of adipic acid, an alcohol component including 100 mol% of ethylene glycol, and 300 ppm of tetraethylammonium hydroxide are mixed to form a mixture. The mixture is heated to 250° C. and subjected to an esterification reaction under a nitrogen atmosphere. When the amount of water distilled reaches a theoretical value for the esterification reaction, 340 ppm of ethylene glycol antimony (as a catalyst) and 100 ppm of trimethyl phosphate (as a thermal stabilizer) are added, and a polymerization reaction is carried out under a vacuum environment of 275° C. to form a third polyester pellet having an intrinsic viscosity of 0.71 dL / g and a glass transition temperature of 27° C.
[0092] Preparation Example 4 The fourth polyester pellet
[0093] An acid component including 95.6 mol% of terephthalic acid and 4.4 mol% of adipic acid, an alcohol component including 69.2 mol% of ethylene glycol, 14.3 mol% of neopentyl glycol and 16.5 mol% of 1,4-butanediol, and 300 ppm of tetraethylammonium hydroxide are mixed to form a mixture. The mixture is heated to 250° C. and an esterification reaction is carried out under a nitrogen environment. When the amount of water distilled reaches the theoretical value of the esterification reaction, 930 ppm of tetrabutyl titanate (as a catalyst) and 100 ppm of trimethyl phosphate (as a thermal stabilizer) are added, and a polymerization reaction is carried out under a vacuum environment of 275° C. to form a fourth polyester pellet having an intrinsic viscosity of 0.68 dL / g and a glass transition temperature of 57° C.
[0094] Preparation Example 5 The fifth polyester pellet
[0095] An acid component including 100 mol% of terephthalic acid, an alcohol component including 75.0 mol% of ethylene glycol, 20.0 mol% of neopentyl glycol and 5.0 mol% of diethylene glycol, and 300 ppm of tetraethylammonium hydroxide are mixed to form a mixture. The mixture is heated to 250° C. and subjected to an esterification reaction under a nitrogen atmosphere. When the amount of water distilled reaches a theoretical value for the esterification reaction, 340 ppm of ethylene glycol antimony (as a catalyst) and 100 ppm of trimethyl phosphate (as a thermal stabilizer) are added, and a polymerization reaction is carried out under a vacuum environment of 275° C. to form a fifth polyester pellet having an intrinsic viscosity of 0.69 dL / g and a glass transition temperature of 73° C.
[0096] Preparation Example 6 Sixth Polyester Pellets
[0097] The preparation method of the sixth polyester pellet of Preparation Example 6 is substantially the same as the preparation method of the first polyester pellet of Preparation Example 1, and the main difference is that the acid component, the alcohol component, the intrinsic viscosity and the glass transition temperature are changed, as shown in Table 2.
[0098] Preparation Example 7 Seventh Polyester Pellets
[0099] The preparation method of the seventh polyester pellet of Preparation Example 7 is substantially the same as the preparation method of the fourth polyester pellet of Preparation Example 4, and the main difference lies in: changing the acid component, the alcohol component, the intrinsic viscosity and the glass transition temperature, as shown in Table 2.
[0100] Preparation Example 8 The eighth polyester pellet
[0101] The preparation method of the eighth polyester pellets of Preparation Example 8 is substantially the same as the preparation method of the first polyester pellets of Preparation Example 1, with the main difference being: changing the acid component, the alcohol component, the intrinsic viscosity and the glass transition temperature, as shown in Table 2.
[0102] Preparation Example 9 The ninth polyester pellet
[0103] The preparation method of the ninth polyester pellet of Preparation Example 9 is substantially the same as the preparation method of the fourth polyester pellet of Preparation Example 4, and the main difference lies in: changing the acid component, the alcohol component, the intrinsic viscosity and the glass transition temperature, as shown in Table 2.
[0104] Preparation Example 10 The tenth polyester pellet
[0105] The preparation method of the tenth polyester pellet of Preparation Example 10 is substantially the same as the preparation method of the first polyester pellet of Preparation Example 1, and the main difference lies in: changing the acid component, the alcohol component, the intrinsic viscosity and the glass transition temperature, as shown in Table 2.
[0106] Test items
[0107] The polyester pellets of Preparation Examples 1 to 10 were subjected to the following tests. For the sake of clarity, the test procedures of the following test items are described using Preparation Example 1 as a representative.
[0108] Intrinsic viscosity (unit: dL / g): Measured according to ASTM D4603 (2003 edition) standard test method for determining intrinsic viscosity of polyethylene terephthalate using a glass capillary viscometer. Take 0.25±0.0025 grams of the first polyester pellets of Preparation Example 1 and add them to 25 mL of a solvent containing 60 wt% phenol and 40 wt% 1,1,2,2-tetrachloroethane to form a mixed solution. Then, heat the mixed solution at 110±10°C for 1 hour and then cool it to form a sample to be tested. Use an Ostwald viscometer to measure the sample to be tested at 25°C, and calculate the intrinsic viscosity using the Huggins equation.
[0109] Glass transition temperature (Tg, unit: °C): The first polyester pellets of Preparation Example 1 were measured using a differential thermal scanning analyzer (brand: TA Instruments; model: 2910 Modulated DSC). The measurement parameters were as follows: the temperature was raised from -50°C to 300°C at a heating rate of 10°C / min to obtain a differential thermal scanning curve. The glass transition temperature was obtained based on the differential thermal scanning curve.
[0110] Table 1
[0111]
[0112]
[0113] Table 2
[0114]
[0115]
[0116] Example 1
[0117] Step (a): Dry the first polyester pellets of Preparation Example 1, the second polyester pellets of Preparation Example 2, and the third polyester pellets of Preparation Example 3 until the moisture content is less than 200 ppm to obtain dried first polyester pellets, dried second polyester pellets, and dried third polyester pellets. Mix 72 wt% of the dried first polyester pellets, 18 wt% of the dried second polyester pellets, and 10 wt% of the dried third polyester pellets to form a polyester mixture. The polyester mixture is melt-treated at 210° C. to 260° C. by a twin-screw extruder, extruded from a T-die, and cooled by winding on a rotating metal roller with a surface temperature of 30° C. to obtain an unstretched sheet with a thickness of 275 μm.
[0118] Step (b-1): The unstretched sheet is preheated by passing it through a preheating roller with a preheating temperature set at 66°C. Subsequently, it is longitudinally stretched along the machine direction at a stretching ratio of 1.4 times by utilizing the speed difference between a first rotating roller with a temperature set at 66°C and a rotation speed of 33.5 m / min and a second rotating roller with a temperature set at 30°C and a rotation speed of 47 m / min. Then, it is annealed by a cooling roller with a temperature set at 30°C to form a longitudinally stretched film.
[0119] Step (b-2): The longitudinally stretched film is passed through a transverse stretching machine at a speed of 47 m / min for preheating treatment, stretching treatment and annealing treatment to form a heat-shrinkable polyester label film with a thickness of 40 μm, wherein the preheating treatment is carried out at a preheating temperature of 92°C, the stretching treatment is carried out at a stretching temperature of 70°C and a transverse stretching ratio of 4.9 times along the perpendicular machine direction, and the annealing treatment is carried out at an annealing temperature of 60°C.
[0120] Example 2
[0121] The preparation methods of Examples 2 to 3 are substantially the same as those of Example 1, with the main difference being that in Example 2, the thickness of the unstretched sheet in step (a) is 196 μm, and step (b-1) is not performed.
[0122] Example 3
[0123] The preparation method of Example 3 is substantially the same as that of Example 1, with the main difference being that in Example 3, the polyester mixture comprises 67 wt% of the dried first polyester particles, 18 wt% of the dried second polyester particles and 15 wt% of the dried third polyester particles, and in step (b-1), the preheating temperature of the preheating roller is set to 62°C, the temperature of the first rotating roller is set to 62°C, and in step (b-2), the stretching temperature of the stretching treatment is set to 67°C.
[0124] Example 4
[0125] The preparation method of Example 4 is substantially the same as that of Example 3, except that the fourth polyester pellets of Example 4 are dried until the moisture content is below 200 ppm to obtain dried fourth polyester pellets. In Example 4, only 100 wt% of the dried fourth polyester pellets are used.
[0126] Example 5
[0127] The preparation method of Example 5 is substantially the same as that of Example 4, with the main difference being that in Example 5, the thickness of the unstretched sheet in step (a) is 196 μm, and step (b-1) is not performed.
[0128] Example 6
[0129] The preparation method of Example 6 is substantially the same as that of Example 1, with the main difference being that the polyester mixture comprises 55 wt% of the dried first polyester particles, 21 wt% of the dried second polyester particles, and 24 wt% of the dried third polyester particles, and in step (b-1), the preheating temperature of the preheating roller is set to 55°C, the temperature of the first rotating roller is set to 55°C, and in step (b-2), the preheating temperature of the preheating treatment is set to 88°C, the stretching temperature of the stretching treatment is 62°C, and the annealing temperature of the annealing treatment is set to 57°C.
[0130] Example 7
[0131] The preparation method of Example 7 is substantially the same as that of Example 3, except that the sixth polyester pellets of Example 7 are dried until the moisture content is below 200 ppm to obtain dried sixth polyester pellets. In Example 7, only 100 wt% of the dried sixth polyester pellets are used.
[0132] Example 8
[0133] The preparation method of Example 8 is substantially the same as that of Example 1, except that the seventh polyester pellets of Example 7 are dried until the moisture content is below 200 ppm to obtain the dried seventh polyester pellets. In Example 8, only 100 wt% of the dried seventh polyester pellets are used.
[0134] Example 9
[0135] The preparation method of Example 9 is substantially the same as that of Example 6, except that the eighth polyester pellets of Example 8 are dried until the moisture content is below 200 ppm to obtain dried eighth polyester pellets. In Example 9, only 100 wt% of the dried eighth polyester pellets are used.
[0136] Comparative Example 1
[0137] The preparation method of Comparative Example 1 is substantially the same as that of Example 5, with the main differences being that in Comparative Example 1, only 100 wt % of the dried first polyester particles are used, and in step (b-2), the preheating temperature of the preheating treatment is set to 98° C., the stretching temperature of the stretching treatment is set to 83° C., and the annealing temperature of the annealing treatment is set to 76° C.
[0138] Comparative Example 2
[0139] The preparation method of Comparative Example 2 is substantially the same as that of Example 5, with the main difference being that in Comparative Example 2, the polyester pellet mixture comprises 90 wt % of dried first polyester pellets and 10 wt % of dried third polyester pellets, and in step (b-2), the preheating temperature of the preheating treatment is set to 92° C., the stretching temperature of the stretching treatment is set to 77° C., and the annealing temperature of the annealing treatment is set to 70° C.
[0140] Comparative Example 3
[0141] The preparation method of Comparative Example 3 is substantially the same as that of Example 1, except that the fifth polyester pellets of Preparation Example 5 are dried until the moisture content is below 200 ppm to obtain dried fifth polyester pellets. In Comparative Example 3, the polyester pellet mixture comprises 18 wt % of the dried second polyester pellets and 82 wt % of the dried fifth polyester pellets.
[0142] Comparative Example 4
[0143] The preparation method of Comparative Example 4 is substantially the same as that of Example 2, with the main difference being that in Comparative Example 4, the polyester pellet mixture comprises 65 wt % of the dried first polyester pellets and 35 wt % of the dried second polyester pellets.
[0144] Comparative Example 5
[0145] The preparation method of Comparative Example 5 is substantially the same as that of Example 1, with the main difference being that in Comparative Example 5, the polyester particle mixture comprises 70 wt % of dried first polyester particles and 30 wt % of dried third polyester particles, and in step (b-1), the unstretched sheet is stretched along the machine direction at a stretching ratio of 1.25 times to form a longitudinally stretched film.
[0146] Comparative Example 6
[0147] The preparation method of Comparative Example 6 is substantially the same as that of Example 3, with the main difference being that in Comparative Example 6, the stretching temperature of the stretching treatment in step (b-2) is 75°C, and the annealing temperature of the annealing treatment is set to 70°C.
[0148] Comparative Example 7
[0149] The preparation method of Comparative Example 7 is substantially the same as that of Comparative Example 2, except that the ninth polyester pellets of Preparation Example 9 are dried until the moisture content is below 200 ppm to obtain dried ninth polyester pellets. In Comparative Example 7, only 100 wt% of the dried ninth polyester pellets are used.
[0150] Comparative Example 8
[0151] The preparation method of Comparative Example 8 is substantially the same as that of Example 6, except that the tenth polyester pellets of Preparation Example 10 are dried until the moisture content is below 200 ppm to obtain dried tenth polyester pellets. In Comparative Example 8, only 100 wt% of the dried tenth polyester pellets are used.
[0152] Table 3
[0153]
[0154]
[0155]
[0156] Table 4
[0157]
[0158]
[0159] [Evaluation items]
[0160] The heat-shrinkable polyester label films of Examples 1 to 9 and the heat-shrinkable polyester label films of Comparative Examples 1 to 8 were evaluated as follows. For the sake of clarity, the test procedures of the following evaluation items are described using Example 1 as a representative.
[0161] Glass transition temperature (Tg, unit: °C) and thermal enthalpy (Hm, unit: J / g) measurement: A thermal differential scanning analyzer (brand: TA Instruments; model: 2910 Modulated DSC) was used to measure the unstretched sheet and heat-shrinkable polyester label film of Example 1. The measurement parameters were as follows: the temperature was raised from -50°C to 300°C, and the heating rate was 10°C / min, to obtain a thermal differential scanning curve. According to the thermal differential scanning curve, the glass transition temperature, the endothermic peak area value and the exothermic peak area value were obtained, and the thermal enthalpy was calculated by a formula, and the formula was: thermal enthalpy = |endothermic peak area value - exothermic peak area value |.
[0162] Measurement of natural shrinkage rate after aging: The heat-shrinkable polyester label film of Example 1 is cut into test samples with a size of 100 mm × 100 mm. The test samples are placed in a hot air oven at 40°C and a relative humidity of 40% for 672 hours for aging treatment to form aged test samples. Then, the aged test samples are taken out of the hot air oven, and the length (LMD) of the aged test samples in a machine direction (abbreviated as MD) and the length (LTD) in a perpendicular machine direction (abbreviated as TD) are measured, and the aging natural shrinkage rate in the perpendicular machine direction (TD aging natural shrinkage rate) and the aging natural shrinkage rate in the machine direction (MD aging natural shrinkage rate) are calculated according to the following formula:
[0163] TD aging natural shrinkage (%) = [(100-LTD) / 100] × 100%
[0164] MD aging natural shrinkage (%) = [(100-LMD) / 100] × 100%
[0165] 55°C shrinkage measurement: According to the JIS Z1709 standard method (2017 updated version), the heat-shrinkable polyester label film of Example 1 is cut into test samples with a size of 100mm×100mm. The test samples are immersed in hot water at 55°C for 10 seconds, 30 seconds, 60 seconds, and 240 seconds to form immersed test samples. At the above immersion time, the immersed test samples are taken out from the hot water and placed in 25°C cold water for cooling. Then, the length (LTD) in a perpendicular machine direction (abbreviated as TD) and the length (LMD) in a machine direction (abbreviated as MD) at the above immersion time are measured, and the shrinkage in the perpendicular machine direction (TD shrinkage at 55°C) and the shrinkage in the machine direction (MD shrinkage at 55°C) at the above immersion time are calculated according to the following formula:
[0166] TD shrinkage at 55°C (%) = [(100-LTD) / 100] × 100%
[0167] MD shrinkage at 55°C (%) = [(100-LMD) / 100] × 100%
[0168] Shrinkage measurement at 95°C for 10 seconds: According to the JIS Z1709 standard method (2017 updated version), the heat-shrinkable polyester label film of Example 1 was cut into test samples with a size of 100 mm × 100 mm. The test sample was immersed in 95°C hot water for 10 seconds to form an immersed test sample. The immersed test sample was taken out from the hot water and placed in 25°C cold water for cooling, and then the length (LTD) in a perpendicular machine direction (abbreviated as TD) and the length (LMD) in a machine direction (abbreviated as MD) were measured, and the shrinkage in the perpendicular machine direction and the shrinkage in the machine direction were calculated according to the following formula.
[0169] TD shrinkage at 95°C (%) = [(100-LTD) / 100] × 100%
[0170] MD shrinkage at 95°C (%) = [(100-LMD) / 100] × 100%
[0171] 55℃30s Shrinkage Force (Unit: N) (Unaged) Measurement: The heat shrinkable polyester label film of Example 1 was cut into test samples with a length of 150 mm in the vertical machine direction and a length of 18 mm in the machine direction. The two ends of the test sample in the vertical machine direction were fixed by a clamp in a shrinkage force machine with a constant temperature water tank (Brand: Jiahe Technology Co., Ltd.; Model: JH-690), and the test sample was immersed in 55℃ hot water at a speed of 800 mm / min for 180 seconds from 200 mm away from the constant temperature water tank to obtain a relationship curve between shrinkage force and time, and the shrinkage force corresponding to 30 seconds was obtained from the relationship curve.
[0172] 55°C 30-second shrinkage force (unit: N) (aging) measurement: The method is similar to the above-mentioned 55°C 30-second shrinkage force (unaged) measurement, except that: the heat-shrinkable polyester label film of Example 1 is cut into test samples with a length of 150 mm in the vertical machine direction and a length of 18 mm in the machine direction, and then placed in a hot air oven at 40°C and a relative humidity of 40% for 672 hours, and then the shrinkage force is measured using the shrink force machine.
[0173] 55℃ 240s Label Debonding Rate (Unaged) Measurement: A water-based adhesive containing 45wt% styrene-butadiene rubber, 40wt% acrylic emulsion, 10wt% ethylene-vinyl emulsion, 0.8wt% sodium hydroxide, 0.1wt% disinfectant, and 4.1wt% water was applied to the heat-shrinkable polyester label film of Example 1 to form a test sample having an adhesive layer with a thickness of 5μm. The test sample was attached to the body of a polyethylene terephthalate bottle with a capacity of 600mL, and then a rubber roller was used to roll the test sample at a speed of 3kg / cm 2 The surface of the sample to be tested was pressed with a pressure of 100°C and rolled back and forth on the surface of the sample to be tested 10 times so that the sample to be tested can be firmly attached to the bottle body. Then, it was left to stand at 25°C for 48 hours to solidify the adhesive layer of the sample to be tested and confirm that the adhesive layer is fixed to the bottle body to form a bottle with a label film. 500 bottles with label films were immersed in a constant temperature water tank filled with hot water at 55°C for 240 seconds. Then, the bottles with label films were taken out of the hot water and the number of bottles with label films that did not detach from each bottle with label films was recorded. Then, the label detachment rate was calculated using the following formula.
[0174] Label removal rate (%) = [(500-number of bottles with undetached label film) / 500] × 100%
[0175] 55°C 240 seconds label removal rate (aging) measurement: The method is similar to the above 55°C 240 seconds label removal rate (unaged) measurement, except that: 500 bottles with label films are placed in a 40°C oven for 144 hours, and then immersed in a constant temperature water tank filled with 55°C hot water for 240 seconds. Then, the bottles with label films are taken out of the hot water, and the number of bottles with label films that have not been detached from each bottle with label films is recorded.
[0176] 80℃120s label removal rate (unaged) measurement: Similar to the above 55℃240s label removal rate (unaged) measurement method, the difference is: the hot water temperature is replaced from 55℃ to 80℃, and the immersion time is replaced from 240s to 120s.
[0177] Table 5
[0178]
[0179]
[0180] Table 6
[0181]
[0182] As shown in Table 5 and Table 6, the shrinkage force of the heat-shrinkable polyester label film of Examples 1 to 9 after being immersed in hot water at 55°C for 30 seconds (regardless of aging) is 5.5 N or more, and the shrinkage rate in the perpendicular machine direction after being immersed in hot water at 55°C for 240 seconds is 50% or more, so the heat-shrinkable polyester label film has an excellent label removal rate after being immersed in hot water at 55°C for 240 seconds. In addition, the heat-shrinkable polyester label film of Examples 1 to 9 also has an excellent label removal rate after being immersed in hot water at 55°C for 240 seconds, because the content of the chain hydrocarbon dicarboxylic acid compound is in the range of greater than 0 mol% to 7 mol%, and the heat-shrinkable polyester label film has a glass transition temperature of 50°C to 65°C, a thermal enthalpy of less than 15 J / g, a shrinkage force of 5.5 N or more after being immersed in hot water at 55°C for 30 seconds, and a shrinkage rate in the perpendicular machine direction after being immersed in hot water at 55°C for 240 seconds is 50% or more.
[0183] On the other hand, in Comparative Examples 1 to 8, in Comparative Example 1, which is equivalent to the contents disclosed in JP3829353B2, US2013 / 0011587A1 and US8815994B2, and under the condition of no chain hydrocarbon dicarboxylic acid compound, the glass transition temperature of the heat shrinkable polyester label film is greater than 65°C, the shrinkage force after immersion in hot water at 55°C for 30 seconds is less than 5.5N, and the shrinkage rate in the perpendicular machine direction after immersion in hot water at 55°C for 240 seconds is 14.7%. Therefore, the label removal rate is not good after immersion in hot water at 55°C for 240 seconds.
[0184] In Comparative Example 2, the glass transition temperature of the heat-shrinkable polyester label film is high, resulting in low shrinkage force after immersion in hot water at 55°C for 30 seconds, low shrinkage rate after immersion in hot water at 55°C for 10 seconds, 30 seconds, 60 seconds or 240 seconds, and a shrinkage force after immersion in hot water at 55°C for 30 seconds of less than 5.5N. Therefore, after immersion in hot water at 55°C for 240 seconds, the label removal rate is poor. In addition, referring to the embodiment of JP3829353B2, it can be seen that the glass transition temperature of the heat-shrinkable polyester label film of Comparative Example 2 is equivalent to that of the embodiment of JP3829353B2. Therefore, even if the glass transition temperature is equivalent, if the shrinkage rate and shrinkage force after immersion in hot water at 55°C for 30 seconds are poor, the label removal rate is still poor.
[0185] In Comparative Example 3, the hydrocarbon-based dicarboxylic acid compound is absent, resulting in low shrinkage when immersed in hot water at 55° C. for 10 seconds, 30 seconds, 60 seconds or 240 seconds. Therefore, the label removal rate is poor when immersed in hot water at 55° C. for 240 seconds.
[0186] In Comparative Example 4, the hydrocarbon-based dicarboxylic acid compound is absent and the thermal enthalpy is higher than 15 J / g, resulting in low shrinkage when immersed in hot water at 55° C. for 10 seconds, 30 seconds, 60 seconds or 240 seconds. Therefore, the label removal rate is poor when immersed in hot water at 55° C. for 240 seconds.
[0187] In Comparative Example 5, the content of the chain hydrocarbon dicarboxylic acid compound is greater than 7 mol %, resulting in a shrinkage force of less than 5.5 N when immersed in hot water at 55° C. for 30 seconds. Therefore, the label removal rate is poor when immersed in hot water at 55° C. for 240 seconds.
[0188] In Comparative Example 6, the annealing temperature is too high, resulting in a shrinkage force of less than 5.5N after aging after immersion in hot water at 55°C for 30 seconds, and a large difference between the shrinkage force before aging and the shrinkage force after aging after immersion in hot water at 55°C for 30 seconds. Therefore, the label removal rate is not good when immersed in hot water at 55°C for 240 seconds.
[0189] In Comparative Example 7, isophthalic acid is used without a chain hydrocarbon dicarboxylic acid compound, resulting in the glass transition temperature of the heat shrinkable polyester label film being too high, the shrinkage force after immersion in hot water at 55°C for 30 seconds being less than 5.5N, and the shrinkage rate after immersion in hot water at 55°C for 240 seconds being less than 50%. Therefore, the label removal rate after immersion in hot water at 55°C for 240 seconds is poor.
[0190] In Comparative Example 8, which is equivalent to Example 2 of US 5070180A, under the condition that the diol compound not including ethylene glycol is not used and the content of the chain hydrocarbon dicarboxylic acid compound is greater than 7 mol%, the heat enthalpy of the heat shrinkable polyester label film is too large, the shrinkage force after immersion in hot water at 55°C for 30 seconds is less than 5.5N, and the shrinkage rate after immersion in hot water at 55°C for 240 seconds is less than 50%. Therefore, the label removal rate is not good after immersion in hot water at 55°C for 240 seconds.
[0191] In summary, through the design of shrinkage force and shrinkage rate, when the heat shrinkable polyester label film of the present invention is attached to a container, the heat shrinkable polyester label film of the present invention can be separated from the container by being immersed in a washing liquid above 50° C., and has a good label removal rate. In addition, through the design of the composition, glass transition temperature, thermal enthalpy and shrinkage force, the heat shrinkable polyester label film of the present invention can also be separated from the container by being immersed in a washing liquid above 50° C., and has a good label removal rate, so the purpose of the present invention can be achieved.
[0192] The above are merely embodiments of the present invention and should not be used to limit the scope of the present invention. All simple equivalent changes and modifications made according to the claims and description of the present invention are still within the scope of the present invention.
Claims
1. A heat shrinkable polyester label film, characterized in that The invention comprises: at least one polyester, wherein the polyester is formed by reacting a composition, and the composition comprises a divalent carboxyl series mixture and a divalent alcohol series mixture, The heat-shrinkable polyester label film has a glass transition temperature of 50° C. to 62° C. and a thermal enthalpy of 15 J / g or less, and the heat-shrinkable polyester label film has a shrinkage force of 5.5 N or more in at least one shrinkage direction when placed in 55° C. hot water for 30 seconds, and a shrinkage rate of 50% or more in the shrinkage direction when placed in 55° C. hot water for 240 seconds; The dicarboxyl-based mixture comprises a dicarboxyl compound and a chain hydrocarbon dicarboxylic acid compound, wherein the dicarboxyl compound is selected from terephthalic acid or dimethyl terephthalate, and based on the total amount of the dicarboxyl-based mixture being 100 mol%, the content of the chain hydrocarbon dicarboxylic acid compound is in the range of greater than 0 mol% to 7 mol%; and The diol mixture includes ethylene glycol and a diol compound, and the diol compound does not include ethylene glycol.
2. The heat shrinkable polyester label film according to claim 1, characterized in that: The chain hydrocarbon dicarboxylic acid compound is selected from a straight-chain hydrocarbon dicarboxylic acid compound, a branched-chain hydrocarbon dicarboxylic acid compound or a combination thereof.
3. The heat shrinkable polyester label film according to claim 2, characterized in that: The straight-chain hydrocarbon-based dicarboxylic acid compound is selected from adipic acid, succinic acid, azelaic acid or any combination thereof.
4. The heat shrinkable polyester label film according to claim 1, characterized in that: The diol compound is selected from a diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group, a branched hydrocarbon diol compound, or a combination thereof.
5. The heat shrinkable polyester label film according to claim 4, characterized in that: The diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group is selected from 1,4-butanediol, diethylene glycol, hexanediol, 1,3-propylene glycol, triethylene glycol, polyethylene glycol or any combination thereof.
6. The heat shrinkable polyester label film according to claim 4, characterized in that: The branched hydrocarbon diol compound is selected from neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol or any combination thereof.
7. The heat shrinkable polyester label film according to claim 1, characterized in that: Based on the total amount of the diol mixture being 100 mol %, the content of the diol compound is greater than 30 mol %.
8. The heat shrinkable polyester label film according to claim 1, characterized in that: When the heat-shrinkable polyester label film is placed in 55° C. hot water for 30 seconds, the shrinkage force in the shrinkage direction is 5.5 N to 10 N.
9. The heat shrinkable polyester label film according to claim 1, characterized in that: The aging natural shrinkage rate of the heat-shrinkable polyester label film is less than 3.2%, and the aging natural shrinkage rate is measured under the conditions of 40° C. and 40% relative humidity for 672 hours.
10. The heat shrinkable polyester label film according to claim 1, characterized in that: The heat shrinkable polyester label film has at least one of the following properties: (1) when placed in hot water at 55°C for 10 seconds, the shrinkage in the shrinkage direction is 5% or more; and (2) When placed in hot water at 55° C. for 30 seconds, the shrinkage rate in the shrinkage direction is 20% or more.
11. The heat shrinkable polyester label film according to claim 3, characterized in that: The heat shrinkable polyester label film has the following properties: When placed in hot water at 95° C. for 10 seconds, the shrinkage rate in the shrinkage direction is 65% or more.
12. A method for preparing a heat shrinkable polyester label film as claimed in claim 1, characterized in that The following steps are involved: (a) forming an unstretched sheet from a polyester component comprising at least one polyester, wherein the polyester is formed by reacting a composition comprising a dicarboxyl-based mixture and a diol-based mixture, The dicarboxyl-based mixture comprises a dicarboxyl compound and a chain hydrocarbon dicarboxylic acid compound, wherein the dicarboxyl compound is selected from terephthalic acid or dimethyl terephthalate, and based on the total amount of the dicarboxyl-based mixture being 100 mol%, the content of the chain hydrocarbon dicarboxylic acid compound is in the range of greater than 0 mol% to 7 mol%; and The diol mixture comprises ethylene glycol and a diol compound, and the diol compound does not include ethylene glycol; and (b) subjecting the unstretched sheet to a preheating treatment, a stretching treatment and an annealing treatment in sequence, wherein the annealing temperature range of the unstretched sheet is from -5°C to +10°C of the glass transition temperature of the unstretched sheet.
13. The method for preparing a heat-shrinkable polyester label film according to claim 12, characterized in that: The chain hydrocarbon dicarboxylic acid compound is selected from a straight-chain hydrocarbon dicarboxylic acid compound, a branched-chain hydrocarbon dicarboxylic acid compound or a combination thereof.
14. The method for preparing a heat-shrinkable polyester label film according to claim 13, characterized in that: The straight-chain hydrocarbon-based dicarboxylic acid compound is selected from adipic acid, succinic acid, azelaic acid or any combination thereof.
15. The method for preparing a heat-shrinkable polyester label film according to claim 12, characterized in that: The diol compound is selected from a diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group, a branched hydrocarbon diol compound, or a combination thereof.
16. The method for preparing a heat-shrinkable polyester label film according to claim 15, characterized in that: The diol compound having a straight-chain hydrocarbon group or a straight-chain hydrocarbon oxy group is selected from 1,4-butanediol, diethylene glycol, hexanediol, 1,3-propylene glycol, triethylene glycol, polyethylene glycol or any combination thereof.
17. The method for preparing a heat-shrinkable polyester label film according to claim 15, characterized in that: The branched hydrocarbon diol compound is selected from neopentyl glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol or any combination thereof.
18. The method for preparing a heat-shrinkable polyester label film according to claim 12, characterized in that: Based on the total amount of the diol mixture being 100 mol %, the content of the diol compound is greater than 30 mol %.
19. The method for preparing a heat-shrinkable polyester label film according to claim 12, characterized in that: In step (a), the polyester component is subjected to a melt treatment and an extrusion treatment to obtain the unstretched sheet, and the temperature range of the melt treatment is 210° C. to 260° C.
20. The method for preparing a heat-shrinkable polyester label film according to claim 12, characterized in that: The stretching process is performed by stretching the unstretched sheet material by 3 to 7 times along a stretching direction, and the stretching direction is a machine direction or a perpendicular machine direction.
21. The method for preparing a heat-shrinkable polyester label film according to claim 12, characterized in that: The stretching treatment is performed by stretching the unstretched sheet along two stretching directions, wherein one stretching direction is the machine direction and the other stretching direction is perpendicular to the machine direction, and the stretching in one of the stretching directions is greater than 1 to 2 times, and the stretching in the other stretching direction is 3 to 7 times.
22. A container, characterized in that The container comprises: the heat-shrinkable polyester label film according to any one of claims 1 to 11 attached to the surface of the container.
Citation Information
Patent Citations
Polyester for heat shrinkable film and preparation method thereof
CN112679709A
Heat-shrinkable polyester film
JP3829353B2
Heat-shrinkable polyester-based film and heat-shrinkable polyester-based label
US20130011587A1
Shrinkable copolyester film
US5070180A
Easily removable label for reusable containers
US6680097B1